PENERAPAN PEMBELAJARAN KOOPERATIF PASANGAN BERBAGI DALAM MENINGKATKAN HASIL BELAJAR IPA DI KELAS 7 B SMP NEGERI 2 JEJAWI - Saleh Rusbandi (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
The classroom  action research with the aim of proving whether by applying the learning model the pair shares in the competency standards of 6 understand of biodiversity with basic competency of 6.2 classifying living thing based on their characteristics and basic competency of 6.3  describe the biodiversity in organizational systems of life from celluler level to the organism can improve the learning outcomes of the students of class 7 B in SMP Negeri 2 Jejawi. This action research was carried out in three rounds (pre cycle, cycle 1 and cycle 2). Each round consists of four stages: design, activity and observation, reflection and revision. The target of this study is students of Class 7 B in SMP Negeri 2 Jejawi. Data obtained in the form of formative test results, observation sheets of teaching and learning activities. Based on the results of the study it can be concluded that the use of sharing partner learning models can improve science learning outcomes for students of class 7 B in SMP Negeri 2 Jejawi with an average student score of 28.33 (pre cycle), 59.79 (cycle I) and 73, 54 (cycle II). Classically, the increase in KKM was 0.00% (pre-cycle), 12.50% (cycle I) and 50% (cycle II). Means that the application of sharing partner learning models can also improve learning achievement classically.Keywords: Natural Science Learning, TPS Type Cooperative Learning Model